2017
DOI: 10.1080/07435800.2017.1294601
|View full text |Cite
|
Sign up to set email alerts
|

Abnormality of adipokines and endothelial dysfunction in Mexican obese adolescents with insulin resistance

Abstract: Our findings demonstrated that the obese adolescents, particularly the obese subjects with IR exhibited increased presence of MetS, abnormality of adipokines, and endothelial dysfunction. The significant interaction between IR and endothelial dysfunction may suggest a novel therapeutic approach to prevent or delay systemic IR and the genesis of cardiovascular diseases in obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Reduced levels of Ad (in particular of its HMW oligomers) have been reported in obese children, compared to normal weight control subjects [63,64,65,66,67]. It has also been reported that male children with persistent obesity have lower Ad levels than those with transient obesity; therefore, low levels of Ad could be a predictor of persistent obesity among boys [68].…”
Section: Adiponectin Obesity and Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Reduced levels of Ad (in particular of its HMW oligomers) have been reported in obese children, compared to normal weight control subjects [63,64,65,66,67]. It has also been reported that male children with persistent obesity have lower Ad levels than those with transient obesity; therefore, low levels of Ad could be a predictor of persistent obesity among boys [68].…”
Section: Adiponectin Obesity and Metabolic Syndromementioning
confidence: 99%
“…Plasma Ad levels are inversely correlated with waist circumference, a marker of abdominal obesity [52]; moreover, weight and waist circumference-to-height ratio are independently associated with plasma Ad concentrations [64]. Other authors demonstrated that waist circumference is an independent determinant of plasma Ad concentration, suggesting that visceral adipose tissue has a central role in reducing circulating levels of Ad [67]. Moreover, high leptin to Ad ratio has been associated with BMI Z-score gain and waist to height ratio gain in non-obese children [68].…”
Section: Adiponectin Obesity and Metabolic Syndromementioning
confidence: 99%
“…The above-described properties of adiponectin were proved in both experimental and clinical studies [17,[48][49][50]. Ortiz Segura MDC et al indicated that the adiponectin concentrations were lower and soluble ICAM-1 levels as markers of endothelium dysfunction were increased in Mexican obese adolescents with insulin resistance compared to those without insulin resistance and in the controls [17]. The results of the research conducted on rat models revealed that the implementation of a high-fat diet leads to continuously increasing of pro-inflammatory cytokines, and decreasing of anti-inflammatory adiponectin levels with the first effects observed after six weeks, while NO levels were decreased at six weeks and lipid peroxidation increased in twelve weeks, which in consequence induced an increase in systolic blood pressure [48].…”
Section: Adiponectin Obesity and Insulin Resistance -When The Vicioumentioning
confidence: 95%
“…The above-described properties of adiponectin were proved in both experimental and clinical studies [17,[48][49][50]. Ortiz Segura MDC et al indicated that the adiponectin concentrations were lower and soluble ICAM-1 levels as markers of endothelium dysfunction were increased in Mexican obese adolescents with insulin resistance compared to those without insulin resistance and in the controls [17].…”
Section: Adiponectin Obesity and Insulin Resistance -When The Vicioumentioning
confidence: 97%
See 1 more Smart Citation